2022
DOI: 10.1177/00914509221127444
|View full text |Cite
|
Sign up to set email alerts
|

Nuancing Drug Harms: Exploring the Context of Substance Use Among Street-Involved Women in Uyo, Nigeria

Abstract: Recent studies on women’s substance use have emphasized the role of structural and environmental contexts in shaping substance use patterns and harms, but the dynamics constitutive of specific substance use contexts are seldom unpacked. This study works with Cameron Duff’s elaboration of context as an assemblage of space, embodiment and practice to explore the contextual dynamics that mediate substance use practices among socially marginalized women. In-depth interviews were used to gather data from a purposiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 64 publications
0
1
0
Order By: Relevance
“…Unfortunately, in our study scenario, the information came from non-medical experts. Studies have shown that social relationships and context have an impact on the choice of non-medical use of drugs (Latkin et al , 2007; Nelson, 2022). The sources of information in this regard are co-workers at the workplace.…”
Section: Discussionmentioning
confidence: 99%
“…Unfortunately, in our study scenario, the information came from non-medical experts. Studies have shown that social relationships and context have an impact on the choice of non-medical use of drugs (Latkin et al , 2007; Nelson, 2022). The sources of information in this regard are co-workers at the workplace.…”
Section: Discussionmentioning
confidence: 99%